1999
DOI: 10.1002/j.1550-8528.1999.tb00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐Induced Cortisol, Mood, and Fat Distribution in Men

Abstract: Stress-induced cortisol, mood, and fat distribution in men. Obes Res. 1999;7:9-15. Objective: A previous study in our laboratory (Moyer et al., Obes Res. 1994;2:255-62 found that, in response to uncontrollable laboratory stress, women with a high waist-to-hip ratio (WHR) had higher cortisol reactivity, poorer coping skills, and lower anger responses than women with low WHR. We aimed to compare high WHR men's stress responses to these women. Research Methods and Procedures:The current study examined cortisol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 36 publications
1
33
0
3
Order By: Relevance
“…22 However, it should also be noted that cortisol responses to acute mental stress have been consistently related to waist/hip ratio in studies of women, 12,40,41 but in men one study observed such an effect while another did not. 14,42 This study has several limitations. The sample consisted of working men and women of Caucasian origin within a limited age range, and results may not generalise to other groups.…”
Section: Discussionmentioning
confidence: 96%
“…22 However, it should also be noted that cortisol responses to acute mental stress have been consistently related to waist/hip ratio in studies of women, 12,40,41 but in men one study observed such an effect while another did not. 14,42 This study has several limitations. The sample consisted of working men and women of Caucasian origin within a limited age range, and results may not generalise to other groups.…”
Section: Discussionmentioning
confidence: 96%
“…Another potential mediator is psychological stress. Evidence from animal models, 37 and more recently from human studies, 38,39 suggests that stress may influence metabolism and body fat distribution. It is plausible that different social groups may be subject to different levels of psychosocial stress (for instance, low employment grade has been linked with increased psychological distress) and this could contribute to increased risk of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Personality and coping could therefore have important bearing on the hypothesis that an inability to handle stress might be one factor leading to hypersensitivity in the HPA axis, setting off neuroendocrine and metabolic disturbances. [36][37][38] Such disturbances may result in greater central fat accumulation that in turn is an important risk factor for cardiovascular disease and diabetes type 2. This is a topic for future research.…”
Section: Personality Traits Among Obese a Rydén Et Almentioning
confidence: 99%